2014
DOI: 10.1097/mib.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Perfusion Measured with Dynamic Contrast-enhanced Ultrasound Predicts Treatment Outcome in Patients with Crohnʼs Disease

Abstract: Article first published online 2 September 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 39 publications
(45 reference statements)
2
53
3
Order By: Relevance
“…To our knowledge, there are no other studies utilizing baseline CEUS as a tool to predict likelihood of response to medical therapy. Other studies investigated the role of posttreatment CEUS kinetic parameters in predicting the outcomes after commencing treatment and reported that follow‐up CEUS could identify nonresponders to medical treatment earlier . Larger studies are required to determine if baseline CEUS quantitative values can independently predict response to treatment and better triage the patients to those who would benefit from escalation or the addition of new treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are no other studies utilizing baseline CEUS as a tool to predict likelihood of response to medical therapy. Other studies investigated the role of posttreatment CEUS kinetic parameters in predicting the outcomes after commencing treatment and reported that follow‐up CEUS could identify nonresponders to medical treatment earlier . Larger studies are required to determine if baseline CEUS quantitative values can independently predict response to treatment and better triage the patients to those who would benefit from escalation or the addition of new treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The use of second-generation US contrast agents combined with low-mechanical-index real-time harmonic US has improved the accuracy of US in evaluating bowel wall vascularization in patients with CD. [8][9][10][11][12][13][14][15][16] Contrast-enhanced US (CEUS) has been used in patients with CD to correlate regional blood volume using a bolus injection method with normal bowel, 8 with color and power Doppler, 9 with endoscopy, 10 and with CDAI. 11 Also, there are a few reports of utilization of bolus CEUS to predict treatment response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, it has been highlighted that colonoscopy can be replaced with noninvasive techniques, such as Doppler ultrasound or CEUS, for the diagnosis of relapsed CD, but more studies are required [39,54,[72][73][74][75]. Doppler examination of the vascularization of thickened bowel wall is useful for the differentiation of relapse from remission and is well correlated with endoscopic findings both in adults, and children [35,43,71].…”
Section: Monitoringmentioning
confidence: 99%
“…A 14 patient study of CE-US showed that delayed contrast wash-in (p ¼ 0.02) and wash-out (p ¼ 0.008) were associated with therapeutic non-response, though no full thickness histology was available. 17 A 39 subject study where patients were dichotomized as being predominantly fibrotic (requiring elective surgery for refractory stricturing disease), or inflammatory (no strictures, but required steroid or anti-TNF), found those judged to be fibrotic had a slower rate of perfusion compared to the inflammatory group (22.6 vs. 45.3 mL/min per 100 mL, p ¼ 0.003). 18 The same group found that the ratio of intestinal tissue perfusion to bowel wall thickness (cutoff of 0.56 mL/min/mm) predicted surgical vs. medically managed disease with an AUROC of 0.92 and sensitivity and specificity 82% and 94%, respectively.…”
Section: Perfusion As a Surrogate For Intestinal Fibrosismentioning
confidence: 99%